Hydrogen-Sulfide-Mediated PpAOS3-JA Module Provides Insight into Salt Stress Resistance in Peach - Xiaolan Gao; Miao Li; Qingtao Gong; Guixiang Li; Haixiang Yu; Xiaomin Dong; Xiaoyou Wang; Zheng Gong; Zhongtang Wang; Yuansong Xiao; Anning Zhang (Plants)
Salt stress is one of the main abiotic stresses that affects peach growth. Hydrogen sulfide has an important role in regulating plant resistance to salt stress. However, the mechanism by which hydrogen sulfide regulates salt stress resistance is currently unclear in peach. Here, we investigated the mechanism by which hydrogen sulfide alleviates salt stress in peach trees. In our study, exogenous hydrogen sulfide enhances the activity of antioxidant enzymes and reduces the accumulation of reactive oxygen species, thereby mitigating salt stress damage to seedlings. Moreover, transcriptome analysis was carried out and an encoding allene oxide synthase gene (AOS), PpAOS3, which is highly responsive to hydrogen sulfide, was found. Overexpression of PpAOS3 increased the root length and jasmonic acid (JA) content and attenuated growth inhibition under salt stress in Arabidopsis. NBT and Evans staining showed that Arabidopsis overexpressing PpAOS3 reduces O2− accumulation and cell death under salt stress. Additionally, transcriptome analysis revealed that 10 genes encoding oxidoreductase were upregulated after hydrogen sulfide treatment. RT-qPCR was also performed which showed that these genes were upregulated to different degrees after hydrogen sulfide treatment. In conclusion, a hydrogen-sulfide-mediated PpAOS3-JA module significantly contributes to salt resistance in peach. These results can serve as a theoretical basis for utilizing hydrogen sulfide to improve the salt tolerance of peach.